2017
DOI: 10.1111/dar.12646
|View full text |Cite
|
Sign up to set email alerts
|

Do needle and syringe programs reduce risky behaviours among people who inject drugs in Kermanshah City, Iran? A coarsened exact matching approach

Abstract: NSPs are a promising approach to reduce injection-related risk behaviours among PWID in Kermanshah, Iran. Expanded coverage of high-quality NSPs is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Our finding is in line with other studies [36,37] showing that the provision of other services from needle and syringe programs, including overdose education and providing naloxone can prevent overdose, [37]. Also, other services include, providing counseling and testing PWIDs about substance abuse treatment, HIV, hepatitis C virus (HCV), HBV counseling and testing [38][39][40][41][42][43], and naloxone for overdose educating PWIDs [44]. Additionally, integrating the health care systems with the services for PWIDs has positive influences both for PWIDs and the society [45,46].…”
Section: Discussionsupporting
confidence: 89%
“…Our finding is in line with other studies [36,37] showing that the provision of other services from needle and syringe programs, including overdose education and providing naloxone can prevent overdose, [37]. Also, other services include, providing counseling and testing PWIDs about substance abuse treatment, HIV, hepatitis C virus (HCV), HBV counseling and testing [38][39][40][41][42][43], and naloxone for overdose educating PWIDs [44]. Additionally, integrating the health care systems with the services for PWIDs has positive influences both for PWIDs and the society [45,46].…”
Section: Discussionsupporting
confidence: 89%
“…The criminalization of drug use has serious public health consequences that adversely impact on the global community [3][4][5]. Previous studies have highlighted the negative health consequences of some drugs for people who use them [6][7][8]. In relation to oral health specifically, there is evidence that people who use drugs (PWUD) have a high sugar intake [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A review by Sawangjit et al also showed that pharmacy-based NSEPs are effective for injection risk behaviors, although the effectiveness on blood-borne disease is still unclear 44 . Noroozi et al conducted a multilevel analysis in Iran and found that NSEPs might reduce HIV risk behavior, as well as injection-related risk behaviors, among PWID 45,46 . Fernandes et al conducted a systematic review and found that NSEP was effective in reducing HIV and injection risk behaviors among PWID 43 .…”
Section: Needle and Syringe Exchange Program (Nsep)mentioning
confidence: 99%